Clinical assortment of preeclampsia in women with diabetes mellitus type 1 during early pregnancy: an investigative analysis - Khalid, Arfa; Akhter, Bilqees; Yazdani, Tehreem; Zohra, Sadaf; Chohan, Shazia Firdos (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the clinical predictors of preeclampsia in T1DM women during first trimester.Study Design: Cross-sectional studyPlace and Duration of Study: Gynaecology and Obstetrics Department of Pakistan Emirates Military Hospital, Rawalpindi, Pakistan, from Dec 2022 to Oct 2023.Methodology: A cross sectional study of 245 T1DM women was conducted in this group. Two categories of women were identified: normal (n=221) and PE (n=24). Clinical data were gathered in the first trimester, and the eGDR, (mg/kg/min) was used to quantify insulin resistance (IR) in the first trimester. Statistical analysis was done to look for variables linked to PE.Results: Preeclampsia was diagnosed in primiparae. The greatest predictor of PE was vasculopathy (OR 28.15 95% CI 8.0-98.6, p=